Kecernaan Nutrien dan Performa Domba Lokal yang Diberi Ransum Kombinasi Berbagai Sumber Protein Berbasis Tongkol Jagung - S Suharti; T Nugroho; I F M Kennedy; L Khotijah (Jurnal Ilmu Nutrisi dan Teknologi Pakan, 2019)
This study aimed to analyze nutrient digestibility of a combination of various protein sources (coconut meal, fish meal and soybean meal) in the concentrate of local rams fed corn cob based diet. Twelve local rams (26.6 ± 1.5 kg BW) fed corn cob based feed were used in this study using in a randomized block design with 4 treatments and 3 replicates. The treatments used were combination of different protein sources namely R1 = combination of coconut and urea cake, R2 = combination of coconut cake and soybean meal, R3 = combination of coconut cake and fish meal, and R4 = combination of coconut, soybean, and fish meal. Data were analyzed by ANOVA and significant differences between treatments were tested by the Duncan Multiple Range Test. The results showed that the combination of various protein sources did not significantly influence the consumption of dry matter and crude fiber, but the used of protein sources of coconut cake and soybean meal significantly increased (p<0.05) intake of organic matter and crude protein. The combination of coconut meal and fish meal (R3) or a combination of coconut cake and soybean meal (R2) increased (p<0.05) nutrient digestibility. Different protein sources do not affect average daily gain (ADG) and feed efficiency . It can be concluded that the use of corn cobs based diet with protein sources combination of coconut meal and fish meal or a combination of coconut cake and soybean meal can increase nutrient digestibility but has not significantly improved body weight and feed efficiency. Keywords: corn cobs, male local sheep, nutrient digestibility, protein sources, sheep performance